1H NMR Fingerprinting of Medicinal Herbs Contain Chemical Drug Material Allopurinol - Adita Yuniati Puspitasari; Harno Dwi Pranowo; Respati Tri Swasono; Tri Rini Nuringtyas (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
A study to differentiate the pure medicinal herbs from the mix medicinal herbs with chemical drug material has been done. For this purpose, we conducted fingerprinting of commercial medicinal herbs and chemical drug material allopurinol using 1H-NMR followed with chemometrics analysis. Nine commercial traditional herbal medicines claimed for rheumatic were used as samples as well as allopurinol as the chemical drug standard. Extraction of samples was done by ultrasonicator for 15 min in methanol-d4 containing 0.01% TMSP as an internal standard. Each type of herbal medicine was prepared in three replicates. The phytochemical analysis was done by 500 MHz JEOL NMR. The chemometrics analysis was done using SIMCA software following the 1H NMR spectra processing with MNOVA software. All spectra showed no contamination with allopurinol. The specific signals of allopurinol at aromatic regions were confirmed not present when the spectra were stacked together. Hence, the result of OPLS-DA analysis convinced that the herbs were clearly separated the medicinal herbs into 3 classes. Jamu 1 is separated from others showed very high intensity of several signals which may indicate an addition of chemical medicines but not allopurinol. The clear separation of other two groups may corresponds to the similarity of ingredients. These results also showed that most of traditional medicines which produced by small industries, the traditional medicines contain no active pharmaceutical ingredients (allopurinol) indicating a high safety of Indonesia traditional medicines.